Prevention of Corruption in Serbian Constitutions up to the First World War - Božović, Jovan (NBP. Nauka, bezbednosti, policija, 2023)
The existence of corruption is closely related to the existence of the state, which ih why the constitution, as the basic legal act of the largest number of states, is particularly significant because measures to prevent corruption can significantly create contidition for the rule of law and the integrity of public bodies. Therefore, in this paper, the study of corruption in Serbia is focused on anti-corruption provisions contained in the Constitution of the Republic of Serbia from 2006 and a comparison with similar proavisions in Serbian constitution from 1835. to the First World War. A brief analysis of the historical context and measures to prevent corruption, shows that the social order at that time, as well as the (non)implementation of the constitution in practice, in itself represented a risk factor for corruption. However, among the anti-corruption provisions of the Serbian constitution, there are some solutions that are more than useful event today.